2011
DOI: 10.1007/s10741-011-9286-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of mineralocorticoid receptor antagonists (MRAs) in very old patients with heart failure

Abstract: Mineralocorticoid receptor antagonists (MRAs) have been effective in reducing total mortality in patients with heart failure (HF) and a reduced left ventricular ejection fraction. Due to the finding that aldosterone levels decrease with age, one might question the effectiveness of MRAs in very old patients (≥80 years of age), those at the greatest risk for developing HF with a preserved left ventricular ejection fraction (PEF). However, while aldosterone levels decrease with age, there is also a decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Glucocorticoid-mediated MR activation occurring in aging persons should be considered in light of the risks for development of heart failure and aging-associated pathologies (Pitt, 2012). Although plasma aldosterone concentration declines with age, cortisol concentration, and the cortisol/cortisone ratio (an indicator of reduced 11HSD2 activity) increases (Henschkowski et al, 2008;Pitt, 2012).…”
Section: E Mineralocorticoid Receptor and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoid-mediated MR activation occurring in aging persons should be considered in light of the risks for development of heart failure and aging-associated pathologies (Pitt, 2012). Although plasma aldosterone concentration declines with age, cortisol concentration, and the cortisol/cortisone ratio (an indicator of reduced 11HSD2 activity) increases (Henschkowski et al, 2008;Pitt, 2012).…”
Section: E Mineralocorticoid Receptor and Agingmentioning
confidence: 99%
“…Although plasma aldosterone concentration declines with age, cortisol concentration, and the cortisol/cortisone ratio (an indicator of reduced 11HSD2 activity) increases (Henschkowski et al, 2008;Pitt, 2012). A cross sectional study of normotensive subjects indicated that 11HSD2 activity declines after the 4th decade of life, favoring cortisol activation of MR and onset of hypertension (Campino et al, 2013).…”
Section: E Mineralocorticoid Receptor and Agingmentioning
confidence: 99%
“…19 Prior studies have demonstrated that MRAs improve clinical outcomes in patients with symptomatic HFrEF 2021 and those with HF or left ventricular (LV) systolic dysfunction complicating myocardial infarction. 22 …”
mentioning
confidence: 99%
“…23-26 Despite these promising preliminary data, 19 no prior large randomized trials have specifically evaluated the effect of an MRA on clinical outcomes in patients with HFpEF. Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) Study is the first large randomized controlled trial of spironolactone versus placebo for HFpEF adequately powered to examine clinical outcomes.…”
mentioning
confidence: 99%
“…In light of the significant cardiovascular benefits of MR antagonism in the aging population, their use in clinical setting is limited by the adverse effects induced by MR blockade on the kidney, such as hyperkalemia, particularly in older patients with reduced renal function and by their anti-androgenic properties (particularly exhibited by spironolactone) which can induce gynecomastia and erectile dysfunction in men (129, 130). Therefore, the current use of MR antagonists is restricted to patients with an estimated glomerular filtration rate >45 mL/min and a plasma potassium concentration of <4.5 mmol/L, in order to avoid the risk of hyperkalaemia (127).…”
Section: Mr Antagonists In the Elderly: Clinical Studiesmentioning
confidence: 99%